Pengembangan Instrumen Penilaian “HOTS” Dari Buku Tematik dengan Menggunakan QUIZIZZ di Sekolah Dasar - agus esti setiani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is motivated by the importance of developing HOTS-oriented assessments, especially on the dimensions of analyze (C4) and evaluate (C5) thinking processes in 21st century learning. The purpose of this study is to(1)explains the process of developing the